Dispatches from Palestine : the rise and fall of the Oslo peace process - Usher, Graham, 1958- (London ; Sterling, Va. : Pluto Press, 1999)
'Usher ... does the best foreign on-the-spot reporting from Palestine.' Edward Said, London Review of Books 'The reader vicariously experiences what will become great moments of popular oral history that official historians will forget in the great scheme of things.' Middle East International.
18 Fatah, Hamas and the Crisis of Oslo: Interviews with Marwan Barghouti and Ibrahim Ghoshah Fatah and the Peace Process: An Interview with Marwan Barghouti -- An Intifada of a Different Kind: An Interview with Ibrahim Ghoshah -- 19 Making Peace: an Interview with Yossi Beilin -- Beilin/ Abu Mazen Understandings -- Beilin/ Eitan National Accord -- Lebanon/ Syria -- 20 Believers in Blue Jeans: an Interview with Rabbi Aryeh Deri -- Shas -- Shas and the Arab Israeli Conflict -- Shas and the Palestinians -- Shas and the Haredim
Includes bibliographical references (pages 176-190) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Arab-Israeli conflict -- 1993- -- Peace; Palestinian Arabs -- Politics and government; Palestine question (1948-); Conflit israélo-arabe -- 1993- -- Paix; Palestiniens -- Politique et gouvernement; HISTORY -- General; POLITICAL SCIENCE -- History & Theory; Arab-Israeli conflict -- Peace; Palestinian Arabs -- Politics and government; Palestijnse kwestie; Vredesonderhandelingen; Since 1993